KEBERAGAMAAN REMAJA PENYALAHGUNA NARKOTIKA (Studi Kasus pada Penganut Beda Agama di Pondok Pesantren Al-Qodir Sleman, Yogyakarta) - Efrida Yanti Rambe (Religi: Jurnal Studi Agama-agama, 2015)
This fi eld research deals with the juvenile religiosity among the narcotic abuse, a casestudy on different religious adherents in Al-Qadir Islamic Boarding School, SlemanYogyakarta. The focus is on how the method of teaching carried out among juvenilenarcotics abuse that based on different religious adherents in Pondok Pesantren Al-Qodir. It includes the religiosity prior to and the aftermath of their relation with thePondok. Applying a qualitative type of approach with an in-depth interview, theresearch shows that, fi rst, the process of nurturing is manifest on the juvenile narcoticsabuse from different religious adherents in the Pondok and second, the religiosity amongthe juveline prior to and the aftermath of their relation with the Pondok PesantrenAl-Qodir is profound.